Applying De Bono’s six thinking hats for an anti-bullying program - Nikolaos Manesis; Natasha Chatzidaki; Marios Gialamas (Intelektual Pustaka Media Utama, 2022)
Bullying among school children is a complex problem that requires a multifaceted approach. De Bono’s six thinking hats technique can help effectively approach the issue of bullying. The innovation of this scenario lies in the fact that it uses De Bono’s technique to deal with bullying at school. In this way, students can gain a holistic knowledge and promote creative and critical thinking in addressing an issue by considering multiple points of view. The purpose of the paper is to present and highlight one more tool, a teaching scenario that uses De Bono’s technique to address the issue of bullying at school. The scenario was implemented in 6th grade students the school year 2021-2022 to develop skills and examine if their attitudes about bullying can be changed. Finally, the students, as they wrote in their evaluation, changed their behavior, reflected, and discussed the problem of bullying and proposed solutions.